2012
DOI: 10.1007/s10616-012-9464-z
|View full text |Cite
|
Sign up to set email alerts
|

Culture, characterization and differentiation of cells from buffalo (Bubalus bubalis) amnion

Abstract: Stem cells present an important tool in livestock assisted reproduction and veterinary therapeutic field such as tissue engineering. We report for the first time isolation of pluripotent stem cell-like cells expressing pluripotency markers (alkaline phospahatase, OCT-4, NANOG and SOX-2) from the amnion of water buffalo (Bubalus bubalis). The cells showed no apparent abnormalities in their chromosomal profiles before and after cryopreservation. The cytochemical staining revealed that pluripotent cells were capa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 30 publications
(30 reference statements)
0
12
0
1
Order By: Relevance
“…Chromosomal spreads at passage 5 and passage 10 revealed that these cells had normal number of chromosomes (2n=50) indicating no apparent changes in ploidy during culture. Previous studies also reported a stable karyotype in cells derived from early buffalo gestation placental tissues (Yadav et al 2011;Dev et al 2012;Mann et al 2013;Singh et al 2013) and term amnion in equine (Seo et al 2013).…”
Section: Discussionmentioning
confidence: 68%
See 2 more Smart Citations
“…Chromosomal spreads at passage 5 and passage 10 revealed that these cells had normal number of chromosomes (2n=50) indicating no apparent changes in ploidy during culture. Previous studies also reported a stable karyotype in cells derived from early buffalo gestation placental tissues (Yadav et al 2011;Dev et al 2012;Mann et al 2013;Singh et al 2013) and term amnion in equine (Seo et al 2013).…”
Section: Discussionmentioning
confidence: 68%
“…In buffalo, Mann et al (2013) reported that cells cultured from AM of gravid uteri of first trimester collected from slaughter house have positive expression of pluripotency markers (alkaline phosphatase, OCT-4, NANOG and SOX-2) and have an osteogenic differentiation potential. An advantage of the present work over Mann et al (2013) is the isolation of somatic cells from term placentae of known pedigree buffalo and gestational stage of the studied amniotic membranes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Em búfalos, estudos demonstraram que MSCs derivadas do âmnio podem ser isoladas e propagadas em cultivo com várias passagens, podendo ter aplicações em diversas áreas como reprodução assistida, desenvolvimento bioló-gico e medicina regenerativa (Yadav et al 2011, Mann et al 2013. Além disso, foi relatado que células derivadas da membrana amniótica expressam pluripotência e marcadores de células-tronco mesenquimais, e são propensos a se diferenciarem em células de linhagem mesenquimal com diferenciação in vitro (Ghosh et al 2015).…”
Section: Cts De Membrana Amniótica Bovina E Bubalinaunclassified
“…,b,c; Mann et al. ), AMSCs expressed NANOG at RT‐PCR, and canine AMSCs were negative (Filioli Uranio et al. , ).…”
Section: Amniotic Membranementioning
confidence: 99%